1998
DOI: 10.1128/jvi.72.7.5648-5653.1998
|View full text |Cite
|
Sign up to set email alerts
|

Protective CD4+and CD8+T Cells against Influenza Virus Induced by Vaccination with Nucleoprotein DNA

Abstract: DNA vaccination is an effective means of eliciting both humoral and cellular immunity, including cytotoxic T lymphocytes (CTL). Using an influenza virus model, we previously demonstrated that injection of DNA encoding influenza virus nucleoprotein (NP) induced major histocompatibility complex class I-restricted CTL and cross-strain protection from lethal virus challenge in mice (J. B. Ulmer et al., Science 259:1745–1749, 1993). In the present study, we have characterized in more detail the cellular immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(69 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…While the hemagglutinin (HA) surface protein is conventionally the primary target of strain-specific influenza DNA vaccines, conserved viral epitopes have the potential to induce immunity against diverse influenza strains. Two highly conserved influenza viral proteins, NP and M2, have been widely targeted as possible broadly protective vaccine candidates [1][2][3][4][5][6][7][8][9]. The main function of the nucleoprotein is encapsidation of the viral genome to form a ribonucleoprotein particle for transcription and packaging.…”
Section: Introductionmentioning
confidence: 99%
“…While the hemagglutinin (HA) surface protein is conventionally the primary target of strain-specific influenza DNA vaccines, conserved viral epitopes have the potential to induce immunity against diverse influenza strains. Two highly conserved influenza viral proteins, NP and M2, have been widely targeted as possible broadly protective vaccine candidates [1][2][3][4][5][6][7][8][9]. The main function of the nucleoprotein is encapsidation of the viral genome to form a ribonucleoprotein particle for transcription and packaging.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the relatively low rate of drift in the NP sequence [5]. Active protection of mice from a lethal challenge with heterotypic influenza A following DNA vaccination with NP has been demonstrated [6]; this protection could be adoptively transferred to naïve mice by CD4 + or CD8 + T cells from immunized mice [7]. Adenoviral vaccines are especially efficient in eliciting strong T cell responses against products of the transgene.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports demonstrated that protective responses elicited by antigens of some viruses that were not present on the surface of the virion, such as the N protein, were more likely to be due to CTLs. For example, nucleoproteins of Ebola virus [4,5], measles virus [6], lymphocytic choriomeningitis virus [7] and influenza virus [8,9] may induce protective CTLs. In porcine coronavirus, transmissible gastroenteritis virus (TGEV), N protein is a representative antigen for the T-cell response and may induce cellular and humoral immune response [10].…”
Section: Introductionmentioning
confidence: 99%